Նզովե՞ս... Եկեղեցական բարձրագույն պատիժների կանոնագիտական վերլուծություն ըստ Հայ եկեղեցական իրավունքի ավանդության - Տ. Շահե Աբեղայ Անանյան; Արամ Մարտիրոսյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Исследование общих и особенных церковных наказаний по сути является отдельной сферой в каноническом праве, где проявляются решения высшей церковной власти к внутренним дисциплинарным кризисам Церкви. The study of the Church’s highest sanctions is, in fact, a distinct domain of Canon Law. It is here that the attitude of the Church’s highest authority vis-à-vis the different canonical and disciplinary crisis in the life of the community or, in some cases even of the Universal Church, is expressively presented.
Keywords: Law; Armenian church; Christianity